Mechanoreceptor Piezo1 Is Downregulated in Multiple Sclerosis Brain and Is Involved in the Maturation and Migration of Oligodendrocytes in vitro - Velasco-Estevez, Maria; Koch, Nina; Klejbor, Ilona; Caratis, Fionä; Rutkowska, Aleksandra (Frontiers in Cellular Neuroscience, 2022)
Mechanical properties of the brain such as intracranial pressure or stiffness of the matrix play an important role in the brain’s normal physiology and pathophysiology. The physical properties are sensed by the cells through mechanoreceptors and translated into ion currents which activate multiple biochemical cascades allowing the cells to adapt and respond to changes in their microenvironment. Piezo1 is one of the first identified mechanoreceptors. It modulates various central nervous system functions such as axonal growth or activation of astrocytes. Piezo1 signalling was also shown to play a role in the pathophysiology of Alzheimer’s disease. Here, we explore the expression of the mechanoreceptor Piezo1 in human MO3.13 oligodendrocytes and human MS/non-MS patients’ brains and investigate its putative effects on oligodendrocyte proliferation, maturation and migration. We found that Piezo1 is expressed in human oligodendrocytes and oligodendrocyte progenitor cells in the human brain and that its inhibition with GsMTx4 leads to an increment in proliferation and migration of MO3.13 oligodendrocytes. Activation of Piezo1 with Yoda-1 induced opposite effects. Further, we observed that expression of Piezo1 decreased with MO3.13 maturation in vitro. Differences in expression were also observed between healthy and multiple sclerosis brains. Remarkably, the data showed significantly lower expression of Piezo1 in the white matter in multiple sclerosis brains compared to its expression in the white matter in healthy controls. There were no differences in Piezo1 expression between the white matter plaque and healthy-appearing white matter in the multiple sclerosis brain. Taken together, we here show that Piezo1-induced signalling can be used to modulate oligodendrocyte function and that it may be an important player in the pathophysiology of multiple sclerosis.